PEMANFAATAN MEDIA SWAY DALAM PEMBELAJARAN DARING UNTUK MENINGKATKAN SEMANGAT BELAJAR SISWA - Waskitorini Waskitorini; Rio Febrianto Arifendi (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
The purpose of this research was to increase students' enthusiasm for learning during online learning. Students feel bored with the type of task given by the teacher which were monotonous. In addition, students are often late in collecting assignments given by the teacher. It takes media or the help of interesting props so that students are excited. Sway media included creative media that can increase students' enthusiasm for learning. This research included classroom action research with the subject of class II students at SDN Simokerto V/138 Surabaya. The results showed that students' enthusiasm for learning had increased. In the first cycle, 72% of students were enthusiastic about participating in learning, increasing to 95% in the second cycle. In addition, the activities of teachers and students also increased. It can be concluded that the use of media sway can increase the learning spirit of class II students at SDN Simokerto V/138 Surabaya.